2019
DOI: 10.3390/toxins11120691
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Abrin-Like and Prepropulchellin-Like Toxin Genes and Transcripts Using Whole Genome Sequencing and Full-Length Transcript Sequencing of Abrus precatorius

Abstract: The sequenced genome and the leaf transcriptome of a near relative of Abrus pulchellus and Abrus precatorius was analyzed to characterize the genetic basis of toxin gene expression. From the high-quality genome assembly, a total of 26 potential coding regions were identified that contain genes with abrin-like, pulchellin-like, and agglutinin-like homology, with full-length transcripts detected in leaf tissue for 9 of the 26 coding regions. All of the toxin-like genes were identified within only five isolated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Thus, it can meet the requirements of genetic studies and analyses of nonmodel plants. In recent years, full-length transcriptome sequencing studies of some plants, such as Dendrobium officinale 32 , Abrus precatorius 33 , and Pogostemon cablin 34 , have been reported. In addition, the published studies have shown that the obtained transcriptome sequences contain large numbers of EST-SSRs 14,35 .…”
mentioning
confidence: 99%
“…Thus, it can meet the requirements of genetic studies and analyses of nonmodel plants. In recent years, full-length transcriptome sequencing studies of some plants, such as Dendrobium officinale 32 , Abrus precatorius 33 , and Pogostemon cablin 34 , have been reported. In addition, the published studies have shown that the obtained transcriptome sequences contain large numbers of EST-SSRs 14,35 .…”
mentioning
confidence: 99%
“…To identify all abrin‐like, prepropulchellin‐like, and agglutinin‐like genes in A. cantoniensis , BLAST searches against the assembled Abrus genome were performed using published abrin and pulchellin sequences (Hovde et al., 2019). Software iqtree was used in phylogeny and cluster analysis of homologous toxin gene.…”
Section: Methodsmentioning
confidence: 99%
“…Abrin poisoning symptoms usually appear only after the incubation period of a few hours to several days with multiple symptoms such as burning in the mouth, difficulty swallowing, nausea, vomiting, among others (Silva et al., 2005). Genomic studies of the Abrus genus firstly focus on Abrus precatorius L. Compared with almost nonposionous (except seeds and pods) A. cantoniensis , A. precatorius is a highly poisonous plant (Hovde et al., 2019). However, the reason for the toxicity differences between these two Abrus species remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is probably due to the difference in stereo structure and heterogeneous glycosylation of the same abrin isoform. In addition, according to previous reports [ 25 ], it would be helpful to elaborate on the content distribution of the four abrin isoforms from the perspective of transcription and genome levels.…”
Section: Resultsmentioning
confidence: 99%